Parallel genetic algorithms for optimizing morphological filters - Kraft, P; Marshall, S; Soraghan, J.J; Harvey, N.R (Fifth International Conference on Image Processing and its Applications, 1995)
Several design methods for parallel genetic algorithms (PGAs) optimizing morphological filters are discussed and an optimal scale and machine independent PGA for a loosely coupled, homogeneous or inhomogeneous multiprocessor computer is developed. The optimization is made in terms of computation speed, parallelization efficiency and quality. Quality means, in this context, the fitness of the best chromosome, which is an objective measure for the performance of the corresponding morphological filter in a particular environment.